Consumer Protection And Supervision of Circulating Goods In Mandailing Natal District - Riski wahdini; Annio Indah Lestari Nasution (Journal of Indonesian Management, 2022)
The purpose of this study iswas to examine consumer protection and control of products circulating in Mandailing Natal Regency in consuming goods or services, the government issued a policy of regulating consumer rights through laws as the implementation of a properous state. As consumers we must know what products an services can be consumed properly. Consumers cannot be separated from the rights and obligations of a producer. In this case the producer is the party that makes or produces the product. And until now, there are still many business actors who deliberately sell produts that are no longer fit for circulation. This study uses a qualitative research method with  a descriptive approach. Law Number 8 of 1999 concerning Consumer protection states that consumer rights in relation to consumer protection for the distribution of health products are the right to comfort, security and safety in obtaining or using these health products. Consumers of health products have the right to correct, clear anda honest information regarding the conditions and guarantees of goods and consumers also have the right to have their opinions heard on the of health products.